Macrodystrophia lipomatosa of the right foot: a case report and treatment - Das, Joydeep (Journal of the Foot & Ankle, 2023)
Macrodystrophia lipomatosa (MDL) is a rare congenital disorder characterized by localized gigantism of one or several digits. It may involve the entire limb due to progressive overgrowth of all mesenchymal elements with an excessive increase in the fibro-adipose tissues. It occurs most commonly in the lower limbs. It comes to clinical attention for cosmetic reasons, mechanical problems secondary to degenerative joint disease, or the development of neurovascular compression. We report a case of MDL of the right foot with difficulty walking and wearing footwear. With a complete radio-clinical workup and history review, a provisional diagnosis of MDL was made, confirmed by histopathology and during surgery. Level of Evidence V; Therapeutic Studies; Expert Opinion.